Circulating insulin-like growth factor-I and indicators of bone and cartilage turnover in steers given trenbolone acetate and estradiol 17-beta alone or in combination - Knetter, Susan Marie (Kansas State University, 2009)
Anabolic steroids are used extensively in beef cattle feeding management to take advantage of well-documented improvements in growth performance and efficiency of implanted cattle. In addition to muscle growth, steroids also impact changes in bone and cartilage formation. In general, these effects can be interpreted as hastening bone aging. The current study was designed to test the hypothesis that recently-identified peripheral indicators of bone and cartilage turnover could be detected in the peripheral circulation. Furthermore, it was hypothesized that these peripheral markers might reflect accelerated aging effects of the widely used steroidal implants trenbolone acetate (TBA) and estradiol-17β (E2). Circulating IGF-I was measured as a positive marker of steroid-induced enhancement of the somatotropic endocrine axis. Thirty-two crossbred yearling steers were blocked by BW and given one of four treatments: non-implanted controls; 25.7 mg estradiol-17beta (E2); 120 mg trenbolone acetate (TBA); or a combination of 120 mg TBA and 24 mg E2 (T+E). Blood samples were collected on d 0, d 7, d 14 and d 28 and serum was analyzed by ELISA for IGF-I concentrations, as well as osteocalcin, C-terminal telopeptides of Type I collagen (CTX-I) and C-terminal telopeptides of Type II collagen (CTX-II), which serve as markers of bone formation, bone resorption and cartilage resorption, respectively. Circulating IGF-I was similar among treatments on d 0 and 28. At d 7 and 14, steers receiving E2 or T+E had greater circulating IGF-I than non-implanted control steers (P < 0.05). In contrast, steers receiving only TBA tended to have elevated IGF-I compared to controls on d 7 and 14 (P = 0.10). Although treatment did not affect serum osteocalcin, concentrations were increased on d 7, 14, and 28 compared to d 0 (P < 0.005 for all). Implant treatment did not affect circulating CTXI, however CTX-II was affected by T+E treatment (P<0.05). The data suggest that, although selected markers of bone and cartilage turnover can be detected in circulation in cattle, implant-induced changes in the concentrations of these markers are not directly evident in the peripheral circulation at least through 28 d following treatment.
Keywords: Bone; Cartilage; Cattle; Estradiol 17-β; Growth; Trenbolone acetate; Agriculture, Animal Culture and Nutrition (0475)